ANALYTICAL METHOD DEVELOPMENT AND VALIDATION OF HPTLC METHOD FOR SIMULTANEOUS ESTIMATION OF SUMATRIPTAN SUCCINATE AND NAPROXEN SODIUM IN PHARMACEUTICAL DOSAGE FORM - P. Parekh, Smruti; Dedania, Zarna R.; Dedania, Ronak; Vijyendraswamy, S. M. (International Journal of Ayurveda and Pharma Research, 2015)
The HPTLC method is based on separation of the two drugs followed by the densitometric measurements of their spots at 277 nm. The separation was carried out on Silica gel 60GF254 using mobile phase Ethylacetate: Methanol: Chloroform: Glacial acetic acid (60:20:19:1 v/v/v/v). The linearity range lies between 250-1500 ng/spot for Sumatriptan Succinate and 1000-6000 ng/spot for Naproxen Sodium with correlation coefficients of 0.997 and 0.996 respectively. The Rf value for Sumatriptan Succinate is 0.49±0.02 and for Naproxen Sodium is 0.28±0.02%. Recoveries of Sumatriptan Succinate and Naproxen Sodium was in the range of 99.54-100.50% and 99.75-100.07% respectively. LOD value for Sumatriptan Succinate was 39.85 ng/spot and for Naproxen Sodium was 80.35 ng/spot. LOQ value for Sumatriptan Succinate was 120.77 ng/spot and for Naproxen Sodium was 243.5 ng/spot. The developed method was validated as per ICH Guidelines.